Tunable filters based on an SOI nano-wire waveguide micro ring resonator - 李帅 吴远大 尹小杰 安俊明 李建光 王红杰 胡雄伟 (Journal of semiconductors, 2011)
Micro ring resonator（MRR） filters based on a silicon on insulator（SOI） nanowire waveguide are fabricated by electron beam photolithography（EBL） and inductive coupled plasma（ICP） etching technology.The cross-section size of the strip waveguides is 450×220 nm2,and the bending radius of the micro ring is around 5μm.The test results from the tunable filter based on a single ring show that the free spectral range（FSR） is 16.8 nm and the extinction ratio（ER） around the wavelength 1550 nm is 18.1 dB.After thermal tuning,the filter＇s tuning bandwidth reaches 4.8 nm with a tuning efficiency of 0.12 nm/℃Meanwhile,we fabricated and studied multi-channel filters based on a single ring and a double ring.After measurement,we drew the following conclusions： during the signal transmission of multi-channel filters,crosstalk exists mainly among different transmission channels and are fairly distinct when there are signals input to add ports.